MACROZOOBENTHIC COMMUNITY STRUCTURES IN SEAWEED CULTURE PONDS IN MUARA GEMBONG ESTUARY, BEKASI , WEST JAVA PROVINCE, INDONESIA - Raden Indarjani; Siti Nurhayati (SEAMEO BIOTROP, 2022)
The study of macrozoobenthic in seaweed culture in Muara Gembong Estuary, Bekasi District, West Java Province, was conducted in May to July 2018. The study was aimed at understanding the roles of macrozoobenthic organisms as ecosystem engineering in seaweed habitat by identifying macrozoobenthic community structures using various biological indices. Sampling sites were conducted at three selected intertidal ponds used for seaweed culture at different distances and perpendicular to the coastline. Samples of macrozoobenthic organisms were collected using an Ekman grab during low tide periods. The study results showed that the macrozoobenthic community from the three ponds were consisted of 9 major benthic families and 14 genera with a total of 139 individuals. The results also showed that gastropod of the genus Cerithiidae was the dominant taxa found in every pond which contributed to 42.45% of the total macrozoobenthic found in the three ponds and became the main contributing taxa to the macrozoobenthic community structure. In addition, genus Platynereis of the Polychaeta Class was found to be another important taxon which contributed to 14.39% of the total macrozoobenthic found in the three ponds. The genus Platynereis were mostly found in the second pond with muddy coarse sandy sediment substrate containing more silt compared to the other two ponds. The rare taxon was the genus Lithophaga from family Mytilidae represented by 1 individual. Our study concluded that the macrozoobenthic community structure in the three ponds was categorized as poorly diverse indicating that the pond system was unstable. The Shannon-Wiener Diversity Index (H’) was only 0.87 on average with the highest diversity index (H’=1.47) was found in the third pond located at the farthest area of the coastline. Meanwhile, the average of Evenness Index was 0.34 indicating that the distribution of the taxa was uneven with a tendency of being dominated by certain taxa.